PERTUMBUHAN TANAMAN GAHARU (Aquilaria spp) YANG DIINOKULASI FUNGI MIKORIZA ARBUSKULA (FMA) DI BAWAH TIGA KONDISI NAUNGAN - Fitriana, Nurul; Muin, Abdurrani; Fahrizal, M (Universitas Tanjungpura, 2017)
The growth of agarwood in open area still not maximum, because agarwood is semitolerance that can not planted in open area, especially at the beginning of its growth. I need to be given some of treatments. The aim of this study to obtain information about mycorrhizal treatment and determine shade intensity to enhance the growth of agarwood (Aquilaria spp) in open area. The research work employed Split Plot Design with Randomized Block Design (RBD) which treatment factors are the type of shading as (main plot) and Arbuskula Mycorrhizal Fungi (AMF) as (sub plot). Variable observation: the growth of height, diameter, number of leaves and percentage of plant life agarwood. The result showed that Mycorrhizal treatment unsignificantly affects to height, diameter, and percentage of plant life, but significantly affect to a number of leaves. The best shade types are 60% paranet and vegetation shade to growth diameter and percentage of plant life. The interaction of plant with AMF under shade showed unsignificantly affect to growth agarwood. Keyword: Agarwood, Arbuskula Mycorrhizal Fungi and shade